A Novel 2.3 Mb Microduplication of 9q34.3 Inserted into 19q13.4 in a Patient with Learning Disabilities. (13th November 2012) - Singh, Shalinder; Ashton, Fern; Marquis-Nicholson, Renate; Love, Jennifer M.; Lan, Chuan-Ching; Aftimos, Salim; George, Alice M.; Love, Donald R.
Abstract : Insertional translocations in which a duplicated region of one chromosome is inserted into another chromosome are very rare. We report a 16.5-year-old girl with a terminal duplication at 9q34.3 of paternal origin inserted into 19q13.4. Chromosomal analysis revealed the karyotype 46, XX, der(19)ins(19;9)(q13.4;q34.3q34.3)pat. Cytogenetic microarray analysis (CMA) identified a ~ 2.3Mb duplication of 9q34.3 → qter, which was confirmed by Fluorescence in situ hybridisation (FISH). The duplication at 9q34.3 is the smallest among the cases reported so far. The proband exhibits similar clinical features to those previously reported cases with larger duplication events.